Hierarchical clustering of the pre-exam anxiety levels in physically inactive and active adolescent students from 56 countries: an observational study using PISA program data - Samuel Encarnação; Samuel Encarnação; Samuel Encarnação; José Eduardo Teixeira; José Eduardo Teixeira; José Eduardo Teixeira; José Eduardo Teixeira; José Eduardo Teixeira; José Eduardo Teixeira; Pedro Forte; Pedro Forte; Pedro Forte; et al. (Frontiers in Sports and Active Living)
IntroductionThe relationship between physical activity and anxiety among students has been extensively studied, with research highlighting the protective effects of physical activity on mental well-being.MethodsThis article synthesizes existing literature on the topic and presents a novel analysis of pre-exam anxiety rates among physically inactive high school students from 56 countries. Using data from the Programme for International Student Assessment (PISA) 2018, a hierarchical clustering method was applied to identify four clusters based on stratified country groups by the students' pre-exam anxiety levels.ResultsThe results indicated five clusters for low physically active students (three with higher anxiety rates and two with lower levels of the condition) and four clusters for the low physically active individuals (two for higher anxiety rates and two for lower levels). Furthermore, the hierarchical model worked with good precision in the clustering task. In conclusion, considering the low physically active students, Brazil (82%) and the Dominican Republic (81%) recorded the highest pre-exam anxiety levels, while the Czech Republic (35%) had the lowest. Among the physically active students, Malaysia (82%), Brazil (81%), and Costa Rica (81%) recorded the highest anxiety levels, whereas again, the Czech Republic (35%) had the lowest.DiscussionThese findings emphasize that although physical activity generally relates to reduced anxiety, this association varies across cultural and educational contexts.